2008
DOI: 10.1002/anie.200801415
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐Rate‐Determining Selectivity in the Terpolymerization of Epoxides, Cyclic Anhydrides, and CO2: A One‐Step Route to Diblock Copolymers

Abstract: Catching a second wind: In kinetic resolution polymerization, one monomer is consumed faster than the other, which creates diblock copolymers that only slowly approach 100 % conversion and contain tapering. In the title reaction, the opposite is true: the first block forms cleanly, followed by a second block that has an even higher rate of polymerization. This unique reaction allows for the programmed self‐assembly of diblock polymers that display little tapering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
218
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(228 citation statements)
references
References 29 publications
9
218
0
1
Order By: Relevance
“…28 In 2008, Coates and co-workers reported that the terpolymerizations of diglycolic anhydride (DGA), CO 2 and cyclohexene oxide (CHO) using catalyst 4b (X = OAc). 29 Detailed in situ ATR-IR spectroscopic analysis revealed that epoxide-anhydride ROCOP occurred first, and, only once the anhydride was nearly completely consumed, did epoxide-CO 2 ROCOP occur. This was surprising because when conducted independently the epoxide-CO 2 copolymerization occurs significantly faster than epoxide-anhydride copolymerization.…”
Section: Copoly(ester-carbonate): Combining Rocop and Rop Processesmentioning
confidence: 99%
“…28 In 2008, Coates and co-workers reported that the terpolymerizations of diglycolic anhydride (DGA), CO 2 and cyclohexene oxide (CHO) using catalyst 4b (X = OAc). 29 Detailed in situ ATR-IR spectroscopic analysis revealed that epoxide-anhydride ROCOP occurred first, and, only once the anhydride was nearly completely consumed, did epoxide-CO 2 ROCOP occur. This was surprising because when conducted independently the epoxide-CO 2 copolymerization occurs significantly faster than epoxide-anhydride copolymerization.…”
Section: Copoly(ester-carbonate): Combining Rocop and Rop Processesmentioning
confidence: 99%
“…[7] In remarkable contrast, insertion reactions into Zn-C bonds are less favored and typically require transitionmetal complexes of electron-rich, late transition metals (Ni, Pd) as effective transmetalation catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…As described in Figure 1, PE and PC can also be obtained by the ring-opening copolymerizartion (ROCOP) of epoxides and anhydrides/carbon dioxide (15,16). Thus, the perfectly alternating copolymerization of epoxides with cyclic anhydrides affords polyesters (17)(18)(19), whereas the perfectly alternating copolymerization of epoxides with carbon dioxide affords polycarbonates (20)(21)(22)(23)(24)(25)(26).…”
Section: Routes For Polyesters and Polycarbonatesmentioning
confidence: 99%
“…Given the success of the ROCOP and ROP routes to polyesters and polycarbonates, research has focussed on combining these two different methodologies to extend the scope of synthetic polymers and enable the synthesis of block copolymers such as poly(ester-co-carbonates) (16,(36)(37)(38)(39)(40)(41). Thus, by combing two ROP processes, Romain et al reported a sequential 'one-pot' synthesis, using a single catalyst, to prepare poly(trimethylene carbonate-co-lactides) featuring a heterotactic PLA block (36).…”
Section: Tandem Catalyses For Poly(ester-co-carbonates)mentioning
confidence: 99%